Strong antimicrobial activity of Hypericum perforatum L. against oral isolates of Lactobacillus spp. - Khadem Nezhad, Sahar; Taghavi Zenouz, Ali; Aghazadeh, Marzieh; Samadi Kafil, Hossein (Cellular and Molecular Biology, 2017)
Lactobacillus spp. are one of the first microorganisms involved in the development of dental caries in the first years of life of the child. The purpose of this study was to investigate the antibacterial effect of alcoholic extract of hypericin against strains of Lactobacillus spp. and determine its related MIC (minimum inhibitory concentration); and cytotoxic effect against gingival fibroblasts. Antimicrobial activity and MIC were evaluated using micro broth dilution method based on CLSI (clinical and laboratory standards institute) protocols. Determination of cytotoxicity was done by using MTT assay protocol on gingival fibroblast cells at 24, 48 and 72 hours after adding different concentrations of alcoholic extract of hypericin. Hypericin extract had an antimicrobial effect on lactobacillus spp., and its MIC was determined to be 0.625µg/ml . The IC50 value after 24, 48 and 72 hours was obtained as 0.89Î¼g/ml, 0.7Î¼g/ml and 0.604Î¼g/ml, respectively. Hypericin extract MIC for L.acidophilus spp. was 0.625µg/ml and given that, MIC was less than IC50. This concentration does not have toxic effects on gingival fibroblast cells. The results of this study indicate that hypericin extract was able to eliminate acid producing strains in the mouth and can be evaluated as a suitable and safe substitute for mouthwashes and oral disinfectants.